CHROMOPHORIC DIVALENT IRON IN OPTICALLY ANISOTROPIC MAGNUSSONITE - Hålenius U.; Lindqvist B. (My University, 1996)
Results from new optical studies of natural magnussonite, including observed weak birefringence and distinct pleochroism, indicate that the symmetry of the mineral structure may be lower than cubic. The optical absorption spectra of natural and synthetic Fe-doped magnussonite crystals are dominated by an absorption band at 15,300 cm-1. The band, which is distinctly polarised (E > O), displays a Beer law relation to sample Fe-content. On the basis of Fe-concentration dependence, band width (ω1/2 = 2,500 cm-1), pressure dependence (Δ ≈ 100 cm-1/GPa) and extinction coefficient, this band is assigned to a spin-allowed electronic d-d transition in Fe2+. An additional absorption band at 14,250 cm-1 assignable to Cu2+ is observed as a relatively weak feature in Cu-rich natural samples. The molar extinction coefficient of the Fe-band is approximately 20 times that of the Cu-band. The presence of a second unresolved Fe2+ d-d band at approximately 3,100 cm-1 is inferred from IR-spectra of a Fe-rich and a Fe-poor magnussonite crystal. A Mössbauer 57Fe spectrum of magnussonite recorded at room temperature reveals a dominating quadrupole doublet, CS = 0.79 and QS = 0.68 mm/s, assignable to ferrous iron in a four-fold planar coordination. The major cause for the colour and pleochroism of green magnussonite is the presence of ferrous iron in comparatively low concentrations. Weaker colours in greenish hues may be produced by the presence of Cu.